2017
DOI: 10.15406/ipcb.2017.02.00023
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ To Be’ Knowledge about Breastfeeding

Abstract: Aim: To assess Portuguese fathers' knowledge on breastfeeding at 28-32 gestational weeks and to examine fathers' knowledge in relation to socio-demographics and paternal characteristics. Design:A cross-sectional design was used. The face-to-face interviewing was used to collected data using a dichotomy clinical instrument composed by 18 knowledge breastfeeding descriptors that emerged from literature review and validated by a panel of experts. The reliability was established using Kuder-Richardson Coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Educating fathers about the benefits of breastfeeding has an effect on the number of mothers choosing to breastfeed; this education is recommended to take place during the antenatal period and the baby's first quarter [11]. Pre-intervention, fathers' knowledge on breastfeeding was low on aspects of exclusive breastfeeding, similar to results of a crosssectional study done involving 143 fathers at health centers in the region of North Portugal indicating a significant lack of breastfeeding knowledge among fathers during pregnancy [12]. In our study, fathers in the intervention group received nutrition education with their expectant partners' antenatal visits, resulting in significantly more fathers in the intervention group being knowledgeable about breastfeeding than the control group post-intervention.…”
Section: Resultssupporting
confidence: 56%
“…Educating fathers about the benefits of breastfeeding has an effect on the number of mothers choosing to breastfeed; this education is recommended to take place during the antenatal period and the baby's first quarter [11]. Pre-intervention, fathers' knowledge on breastfeeding was low on aspects of exclusive breastfeeding, similar to results of a crosssectional study done involving 143 fathers at health centers in the region of North Portugal indicating a significant lack of breastfeeding knowledge among fathers during pregnancy [12]. In our study, fathers in the intervention group received nutrition education with their expectant partners' antenatal visits, resulting in significantly more fathers in the intervention group being knowledgeable about breastfeeding than the control group post-intervention.…”
Section: Resultssupporting
confidence: 56%
“…Similar to our study at baseline, a cross-sectional study was done in Brazil that assessed paternal breastfeeding knowledge during pregnancy. The findings showed a lack of breastfeeding knowledge among the fathers with a specific knowledge deficit on how to manage breastfeeding complications, promote lactation and assure a proper latch [16]. Our findings indicated an increase in knowledge on infant feeding by fathers when fathers were exposed to nutrition education.…”
Section: Discussionmentioning
confidence: 68%
“…The systematic review indicated that all of the studies were from middle‐income countries; no intervention studies focused on low‐income countries. According to Abera, Abdulahi, and Wakayo () and Cardoso, Silva, and Marin (), involving fathers in breastfeeding support significantly enhances mother's perceptions of breastfeeding and can potentially optimize breastfeeding rates, exclusivity, and duration. Therefore, with the changing role of fathers in low‐income countries, there is a potential opportunity for fathers to maximize the health of their children by supporting their partners using their breastfeeding knowledge to motivate and assist them to breastfeed (Rempel & Rempel, ).…”
Section: Discussionmentioning
confidence: 99%